Apraxia and the Fetal Posterior Cerebral Artery. Case presentation - Ariagna Martinez Chile; Angel Santos-Martinez; Enrique José Esteban-Garcés (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Apraxia is a group of non-paralytic disorders of motor function, where the person loses the ability to execute learned voluntary movements, without significant muscle weakness. It has been related to lesions of the frontal and parietal lobes. The most frequent causes are: vascular, tumors, and trauma, the first being the most prevalent in our environment. The middle cerebral artery is responsible for supplying these structures. Objective: To highlight the importance of clinical findings and complementary tests in the topographic and etiological diagnosis of stroke. Clinical case: Here, we report the case of a 68-year-old man suffering from hypertension, diabetes and dyslipidemia who presented a picture of left hemiparesis, kinetic apraxia, and homonymous hemianopsia; a neurological focus that usually corresponds to and is attributed to the vascular territory of the middle cerebral artery of the right hemisphere, associated with absence of flow in the homonymous proximal internal carotid artery and evidenced by Doppler. Conclusions: Strokes from the fetal posterior cerebral artery territory can clinically mimic the middle cerebral artery and present with an apraxic disorder as a cardinal manifestation; hence the importance of a careful review of the complete neuroimaging study in all cases.